Using the Hierarchical Taxonomy of Psychopathology (HiTOP) as a Framework to Dimensionally Map Neurodevelopmental Disorders. - Dow, Khaiden S. (Curtin University, 2023)
Mental disorders are organised via the categorical framework of the DSM-5-TR, which has several issues (e.g., extensive co-occurrence). However, evidence alternatively supports the Hierarchical Taxonomy of Psychopathology (HiTOP), a dimensional framework of mental disorders. We extended the HiTOP by considering the dimensional position of Neurodevelopmental disorders and related experiences, and found that they generally fitted under existing HiTOP domains (i.e., autism under Detachment, ADHD under Disinhibition, and specific learning disorder and tic disorders under Psychoticism).